A systematic review and meta-analysis on the effects of statins on pregnancy outcomes. (November 2021) - Vahedian-Azimi, Amir; Bianconi, Vanessa; Makvandi, Somayeh; Banach, Maciej; Mohammadi, Seyedeh Momeneh; Pirro, Matteo; Sahebkar, Amirhossein
Abstract: Background and aims: Statins are contraindicated in pregnancy, due to their potential teratogenicity. However, data are still inconsistent and some even suggest a potential benefit of statin use against pregnancy complications. We aimed to investigate the effects of statins on pregnancy outcomes, including stillbirth, fetal abortion, and preterm delivery, through a systematic review of the literature and a meta-analysis of the available clinical studies. Methods: A literature search was performed through PubMed, Scopus, and Web of Science up to 16 May 2020. Data were extracted from 18 clinical studies (7 cohort studies, 2 clinical trials, 3 case reports, and 6 case series). Random effect meta-analyses were conducted using the restricted maximum likelihood method. The common effect sizes were calculated as odds ratios (ORs) and their 95% confidence interval (CI) for each main outcome. Results: Finally, nine studies were included in the meta-analysis. There was no significant association between statin therapy and stillbirth [OR (95% CI) = 1.30 (0.56, 3.02), p= 0.54; I 2  = 0%]. While statin exposure was significantly associated with increased rates of spontaneous abortion [OR (95% CI) = 1.36 (1.10–1.68), p= 0.004, I 2  = 0%], it was non-significantly associated with increased rates of induced abortion [OR (95% CI) = 2.08 (0.81, 5.36), p= 0.129, I 2  = 17.33%] and elective abortion [OR (95% CI) = 1.37 (0.68, 2.76), p= 0.378, I 2  = 62.46%]. A non-significant numerically reduced rate of preterm delivery was observed in statin users [OR (95% CI) = 0.47 (0.06, 3.70), p= 0.47, I 2  = 76.35%]. Conclusions: Statin therapy seems to be safe as it was not associated with stillbirth or induced and elective abortion rates. Significant increase after statin therapy was, however, observed for spontaneous abortion. These results need to be confirmed and validated in future studies. Graphical abstract: Image 1 Highlights: Statins are contraindicated in pregnancy but there are controversies over their safety. We aimed to investigate the effects of statins on pregnancy outcomes through a meta-analysis. Nine studies were included in the meta-analysis. Statin theray was not associated with stillbirth and induced and elective abortion. Significant increase after statin therapy was observed for spontaneous abortion.